50 Years of CMJ: The First Decade. (1st January 2020) - Klyve, Dominic
Abstract : Editor's Note: As of this issue, The College Mathematics Journal has published fifty completed volumes. To celebrate 50 years of continued excellence in publishing expository mathematics, pedagogical discussions, and more, we plan to use two pages in each of the five issues of 2020 to tell the story of one decade of the journal. Some of these pieces will be written by people who were personally involved with CMJ during that time, so watch this space for some familiar names!